2021
DOI: 10.21744/ijhms.v5n1.1808
|View full text |Cite
|
Sign up to set email alerts
|

Family care model development in treating schizophrenia patients that have self-deficit nursing based system

Abstract: The purpose of this study is to develop a family care model in treating schizophrenia patients who experience self-deficit based on the nursing system during the COVID-19 pandemic. Explanatory research design with cross-sectional approach. The population in this study were all families of schizophrenic patients in two mental health institutions in Bangkalan, Indonesia with a total sample of 72 families. The research instrument used was a re-control checklist sheet and a questionnaire about family factors and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Among the malignant lesions, mucoepidermoid was the most common constituting about 14% of cases. Similar observations were reported by Sharma M et al (2017)7 , Yogambal et al (2015)2 , Kakoty S et al (2017)5 , S V Ramana et al (2017)8 . It has a diagnostic accuracy of 66% which is significantly more than other studies.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Among the malignant lesions, mucoepidermoid was the most common constituting about 14% of cases. Similar observations were reported by Sharma M et al (2017)7 , Yogambal et al (2015)2 , Kakoty S et al (2017)5 , S V Ramana et al (2017)8 . It has a diagnostic accuracy of 66% which is significantly more than other studies.…”
supporting
confidence: 80%
“…Kakoty et al (2017) 5 reported an incidence of 44% of cases and Sharma et al (2015) 6 reported an incidence of 68.7% of the total cases of pleomorphic adenoma. The present study showed a diagnostic accuracy of 87 % for pleomorphic adenoma, which were significantly better than that observed in the Malaysian J Pathol (2017) 3 reported a diagnostic accuracy of 76% of the total cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fourth study dealt with the experiences lived by the inmates who were infected with COVID-19, who mention that the symptoms presented during the disease were mild and pointed to the lack of supplies in the first months of the pandemic and the incorrect use as a cause of contagion (Clifton & Mann, 2011;McCaughey & Traynor, 2010;Kumaran & Carney, 2014). of personal protection equipment; Concerning mental health, they experienced fear and concern about the prognosis of the disease and subsequent rejection by their relatives for considering them a source of contagion even though they had already overcome the disease; this is the only study in which it is mentioned that the students received support and follow-up from the university student welfare unit and from the institution in which they served (Sisalema, 2021;Amir et al, 2021).…”
Section: The Situation Of the Nursing Intern During The Covid-19 Pand...mentioning
confidence: 99%
“…Aypay (2011) adapted the latest scale to Turkish learners, but despite the satisfactory results of the statistical analysis, the factors were not consistent with Turkish culture (40). Schraw, Bendixen&Dunkle (2002) designed and validated another tool for examining the epistemic beliefs inventory with 28 items (41). Compared to Schumer's Epistemological Beliefs Questionnaire, this tool was more stable and accurate in terms of few items and could estimate the dimension of knowledge source that was not determinable and measurable in Schumer's Epistemological Beliefs Questionnaire.…”
Section: Introductionmentioning
confidence: 99%